An RNA Virome Associated to the Golden Orb-Weaver Spider Nephila clavipes - Debat, Humberto J. (Frontiers in Microbiology, 2017)
The golden orb-weaver spider Nephila clavipes, known for its sexual size dimorphism, is abundant and widespread in the New World. The first annotated genome of orb-weaver spiders, exploring N. clavipes, has recently been reported. The study, focused primarily on the diversity of silk specific genes, shed light into the complex evolutionary history of spiders. Furthermore, a robust transcriptome analysis provided a massive resource for N. clavipes RNA survey. Here, I present evidence of viral sequences corresponding to the first 10 extant virus species associated to N. clavipes and indeed, nephilids. The putatively new species are linked to ssRNA positive-strand viruses, such as Picornavirales, and to ssRNA negative-strand and dsRNA viruses. In addition, I detected sequence data of new strains of two recently reported arthropod viruses, which complemented and extended the corresponding sequence references. The identified viruses appear to be complete, potentially functional, and presenting the typical architecture and consistent viral domains. The intrinsic nature of the detected sequences and their absence in the recently generated genome assembly, suggest that they correspond to bona fide RNA virus sequences. The available RNA data allowed for the first time to address a tissue/organ specific analysis of virus loads/presence in spiders, suggesting a complex spatial and differential distribution of the tentative viruses, encompassing the spider brain and also silk and venom glands. Until recently, the virus landscape associated to spiders remained elusive. The discovered viruses described here provide only a fragmented glimpse of the potential magnitude of the Aranea virosphere. Future studies should focus not only on complementing and expanding these findings, but also on addressing the potential ecological role of these viruses, which might influence the biology of these outstanding arthropod species.